High Resolution Radar Imaging On Synthetic And Natural Objects - Chiang , Chun Tong (2005)
A three dimensional (3-D) radar image can be contructed from (2-D) scanning microwave measurements. A Vector Network Analyzer (VNA) has been used for wideband phase and magnitude measurements of radar return. Quasi-monostatic horn antenna configuration is chosen to transmit and receive the electromagnetic wave. Measured target is placed on a polystyrene foam pedestal at 5 meters distance away from the 2-D planar scanner. A wide bandwidth, ranging from 3 GHz to 18 GHz gives rise to high range resolution. A time domain gating technique is used to remove spurious signals from the desired signal of the radar target.